Corruption Perception Index (CPI)- Satu Tinjauan Awal di Malaysia - Nurul Liliy Suzani Jalal; Abd. Hakim Mohad @ Mohamad Ramli (USIM Press, 2024)
E-Proceeding Islamic Science Social Postgraduate Conference 2023 (ISSPeC 2023) “The Tradition of Knowledge as a Catalyst for the Sustainability of Civilization”/ editors : Anita Binti Ismail, Farah Laili Binti Muda @ Ismail, Kamal Azmi Bin Abd Rahman, Afi Roshezry Bin Abu Bakar, Ikmal Hafiz Bin Jamal Organized by: Institut Sains Islam (ISI) & Pusat Pengajian Teras (PPT) 30 November 2023